GAGASAN PENGATURAN SANKSI PIDANA KEIMIGRASIAN TERHADAP KORBAN TINDAK PIDANA PENYELUNDUPAN MANUSIA - Limonang, Limonang; Firdaus, Emilda; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
People smuggling as organized crime has been discussed in the United Nations Convention Againt Transnational Organized Crime or the UN Convention against Organized Transnational Crimes was finally ratified through Law Number 5 of 2009 in order to strengthen international cooperation and be increased in order to prevent and eradicate transnational organized crime. In the process, people who want to be smuggled migrant victims usually give a smuggler reward. In other words, people who are smuggled do their actions consciously and know the consequences of their actions. The modus operandi of human smuggling is inseparable from problems of demand (demand) and supply (payment). The smugglers will facilitate those who can afford to pay, then find an intermediary then the ship's captain and the person who will make fake documents if needed.This type of research can be classified in the type of Normative legal research, which reveals legislation relating to legal theories that are the object of research. The approach taken uses a qualitative analysis approach by looking for data both in books, journals and other scientific works related to this research. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the results of the study are: First, the Legal Arrangement of Human Trafficking Crimes According to Law Number 6 Year 2011 concerning Immigration has been regulated in general but in the norms the Immigration Act does not clearly explain the position of victims as perpetrators and regarding the crime of human smuggling is only explained in general terms. Second, the Ideal Immigration Criminal Sanction Arrangement Against Victims of Human Trafficking in Indonesia already has immigration rules but there is no specific article or special section governing human smuggling, the purpose of this special regulation is because the criminal acts of smuggling are different from acts of smuggling criminal immigration because it has a broad offense element and a concrete definition.Keywords: People Smuggling, Crime, Victim, Immigration, Rules.